Globalization, Mobility and Air Connectivity Analysis: a Tool for Interdisciplinary Practice - Córdoba Ordóñez, Juan Antonio; Gago García, Cándida (Revista de Antropología Social, 2012)
This paper explores the interconnected relationship between Geography and Social Anthropology in the study of social and spatial phenomena. It argues that the informed and combined use of quantitative and qualitative research techniques, like air connectivity analysis and ethnographic fieldwork, are fundamental in the understanding of socioeconomic globalization processes, and particularly in those characterized by mobility. The study of air mobility in Mexico highlights the existence of multi-scalar and multi-functional patterns of relations that are vital to explain the situated dynamics of the social and territorial relations that have followed the country’s adoption of neoliberal policies. And specifically, to analyze processes as regional adjustments, labour migration, tourism, development and underdevelopment, spatial fixation, as well as homogenization and cultural hybridization.